Estudio de prefactibilidad para la instalación de una planta productora de mantequilla condimentada en tres presentaciones: ajos, mix hierbas y ajos y finas hierbas en envase lápiz untable - Suarez Saldaña, Dyana Allison (2023)
This pre-feasibility study verifies the market, technical, economic, and social viability for the installation of a production plant for butter flavored with garlic and fine herbs in stick containers. In this way, this objective was achieved through the analysis of the following chapters of the study. The first chapter covers the description of the problem, as well as the hypothesis and respective justifications of the study. In the second chapter, the target audience for the product was determined, as well as the calculation of the project's demand for the horizon of the study, being 133 236 units of Melty butter in the last year. In addition to this, the necessary marketing and distribution strategies were established to increase the company's income. In the third chapter, for the evaluation of the location of the plant was used the Ranking de factores method. Which resulted as an optimal location to Ate, Lima Metropolitana. Thanks to the analysis and qualification of the most influential factors for a good plant operation. In the fourth chapter, the different plant sizes were evaluated: market, productive resources, technology, and equilibrium point. Of which, the determining plant size was market, as it was above the minimum size required to generate profit and below the size of productive and technological resources. In the fifth chapter, the production process to produce butter seasoned in stick packaging was defined; from this, the necessary technology was selected and consequently the bottleneck of the process was found, being the milk cream ripening. In addition, the quality, maintenance, occupational health and safety and environmental management plan were defined. Also, the Guerchet method was used to find the minimum recommended area for the productive zone; and, with respect to the other spaces, the National Building Regulations were used as a guide. In the sixth chapter, the organizational structure of the company was defined through an organization chart, which reflects the jobs necessary for the optimal functioning of the organization. In the seventh chapter, the total investment required for the installation and operation of the plant was estimated. From this, the economic and financial viability of the project could be evaluated through indicators such as VANF (S/285 846,34), TIRF (46,78%), R B/C (2,22 times) and PR (2 year and 9 months) obtaining positive results that safeguard the decision to invest in the project. Additionally, a sensitivity analysis was performed using different scenarios, in which the fluctuation of the most representative variables of the study model was evaluated. Finally, in the eighth chapter, an analysis of the social impact of the company was carried out through indicators such as value added, capital intensity and density, and the capital product ratio. Obtaining positive results that represent a benefit for the communities and entities involved.